Generation of Heritable Prominent Double Muscle Buttock Rabbits via Novel Site Editing of Myostatin Gene Using CRISPR/Cas9 System - Zheng, Yalin; Zhang, Yu; Wu, Liyan; Riaz, Hasan; Li, Zhipeng; Shi, Deshun; Rehman, Saif ur; Liu, Qingyou; Cui, Kuiqing (Frontiers in Veterinary Science, 2022)
Rabbits have been domesticated for meat, wool, and fur production, and have also been cherished as a companion, artistic inspiration, and experimental model to study many human diseases. In the present study, the muscle mass negative regulator gene myostatin (MSTN) was knocked out in rabbits at two novel sites in exon3, and the function of these mutations was determined in subsequent generations. The prominent double muscle phenotype with hyperplasia or hypertrophy of muscle fiber was observed in the MSTN-KO rabbits, and a similar phenotype was confirmed in the F1 generation. Moreover, the body weight of MSTN-KO rabbits (3708 ± 43.06g) was significantly higher (P <0.001) at the age of 180 days than wild-type (WT) rabbits (3224 ± 48.64g). In MSTN-KO rabbits, fourteen rabbit kits from the F1 generation and thirteen of the F2 generation stably inherited the induced MSTN gene mutations. Thus, we successfully generated a heritable double muscle buttocks rabbits via myostatin mutation with CRISPR/Cas9 system, which could be valuable in rabbit’s meat production and also a useful animal model to study the development of muscles among livestock species and improve their important economic traits as well as the human muscle development-related diseases.